Separation of nadolol stereoisomers by liquid chromatography using Chiralpak IA chiral stationary phase - Arafah, Rami (2015)
The main objective of this work is to study the chiral separation of stereoisomers of nadolol by preparative liquid chromatography. In this report it is presented the state of the art and experimental results obtained for optimizing the methodology for preparative scale separation of nadolol stereoisomers using an immobilized chiral stationary phase (Chiralpak® IA). The screening of the solvent composition is based on the best solvent or solvents mixture to perform the pseudo-binary separation (1+2+3/4) of the more retained stereoisomer using the simulated moving bed technology. The three least retained components (1, 2 and 3) co-elute in the raffinate outlet stream and the more retained component (4) will elute in the extract outlet stream. After the solvent composition optimization, 100%methanol:0.1%diethylamine solvent composition was selected to perform the experimental SMB separation. Experimental results also include adsorption equilibrium isotherm and breakthroughs measurements followed by SMB experimental operation. Using a 2 g/L total feed concentration, the more retained stereoisomer was totally recovered at the extract outlet stream with 100% purity, obtaining a system productivity of 0.31 gtarget product/(Lbed.hr) and requiring a solvent consumption of 27.71 Lsolvent/gtarget product. Another SMB run was performed using a considerable higher feed concentration of 10 g/L and an improvement in the performance parameters were observed. For the more retained stereoisomer in the extract outlet stream, a purity of 99.5%, and a recovery of 97.6% was obtained, with a productivity of 1.98 gtarget product/(Lbed.hr) and a solvent consumption of 3.13 Lsolvent/gtarget product. The extract and raffinate SMB outlet streams were collected and used to perform additional adsorption equilibrium isotherm and breakthroughs experiments. These results were used to evaluate the differences in the adsorption equilibrium dynamics for pure and racemic nadolol feed mixtures. This work introduced new alternative results for the separation of nadolol stereoisomers and contributed for a future objective of the complete separation of the four nadolol stereoisomers by SMB technology using different modes of SMB operation, adsorbents and solvent compositions.